Clinicophysiological and haemodynamic effects of fentanyl with dexmedetomidine in halothane and isoflurane anaesthetized buffaloes - SINGH, G D; KINJAVDEKAR, P; AMARPAL, AMARPAL; AITHAL, H P; PAWDE, A M; SINGH, JASMEET (The Indian Journal of Animal Sciences, 2013)
The clinical, physiological, haemodynamic and anaesthetic effects of halothane and isoflurane in buffaloes premedicated with dexmedetomidine and fentanyl, were studied. Clinically healthy male buffaloes (6) were used. All the animals received 2 treatments randomly at weekly interval in groups H (halothane) and I (isoflurane). In both groups sedation was accomplished by fentanyl (5 μg/kg body wt) and dexmedetomidine (5 μg/kg body wt) intravenously. Induction of anaesthesia was achieved by 5% thiopental sodium in both groups. Maintenance of anaesthesia was done by halothane in group H and by isoflurane in group I respectively in 100% oxygen through a large animal anaesthesia machine. The different treatments were evaluated on the basis of clinical, physiological, haematological, biochemical and haemodynamic parameters. It is concluded that dexmedetomidine-fentanyl-thiopental and isoflurane provided better clinical, physiological and haemodynamic stability than dexmedetomidine-fentanyl-thiopental and halothane in buffaloes.